Pengaruh Kepemimpinan Transformasional Kepala Sekolah, Kompensasi dan Motivasi Kerja Guru terhadap Mutu Pendidikan di SMPS Sub Rayon 3 Kabupaten Jepara - Waraningtyas, Dyah Tuti; Yuliejantiningsih, Yovitha; Sudana, I Made (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
This research was motivated by the problem of less than optimal leadership of school principals, teacher compensation and teacher motivation at SMPS Sub-rayon 3 Jepara district. The aim of this research is to determine and analyze: (1) the influence of the principal's transformational leadership on the quality of education; (2) the influence of compensation on the quality of education; (3) the influence of teacher work motivation on the quality of education; (4) the influence of the principal's transformational leadership, compensation, teacher work motivation together on the quality of education at SMPS Sub-rayon 3 Jepara district. This research approach is quantitative research with an ex post facto non-experimental type of research. The population in this study were SMPS teachers in Sub-rayon 3 Jepara district with a sample of 139 people using proportional random sampling techniques. The data collection method uses a questionnaire method. The data analysis used is descriptive analysis, requirements testing and hypothesis testing using simple linear regression analysis and multiple linear regression with the SPSS 20 program. Based on the research results, it was found that: (1) there is no significant influence of the principal's transformational leadership on the quality of education at SMPS Sub-rayon 3 Jepara. (2) there is an influence of compensation on the quality of education at SMPS Sub-rayon 3 Jepara with a sig value less than the probability, namely 0.015 < 0.05. (3) there is a simultaneous influence of work motivation on the quality of education with a value of 0.000<0.05 and an influence of 11%. (4) there is a simultaneous influence of transformational leadership variables, compensation and work motivation of 12.9%. The principal's transformational leadership variable provides an effective contribution (SE) of -0.00594%, compensation is 2.95% and work motivation provides an effective contribution (SE) of 9.97% with a total effective contribution of 12.914%. Furthermore, the principal leadership variable provides a relative contribution (SR) of -0.046%, compensation is 22.8% and work motivation provides a relative contribution (SR) of 77.28% with a total relative contribution of 100%. It is recommended that school principals improve and understand transformational leadership, teacher compensation and teacher work motivation in realizing quality education.